CAPACITY OF INDONESIAN FOREST AS CO2 SINK: COMPARING AN INTACT PRIMARY FOREST OF LORE LINDU NATIONAL PARK CENTRAL SULAWESI WITH DEGRADED AND DRAINED PEATLAND FOREST IN CENTRAL KALIMANTAN - Tania June (Agromet, 2010)
This article compares the capacity of undisturbed tropical forest in absorbing COand acts as a net sink with the disturbed (drained) peatland forest acting as a net source.  Undisturbed forest of Lore Lindu National Park (LLNP) absorbs substantial amount of CO22  with  low ecosystem respiration resulted in a net absorbtion reaching -970 gCm-2 year-1.  Data from a disturbed peatland forest in Central Kalimantan shows that although absorption was higher than the LLNP area ecosystem respiration of this drained peatland resulted in a big net emission reaching 447 gCm-2 year-1.  Recovery of the hydrological system of the area, reduced emission substantially.This article compares the capacity of undisturbed tropical forest in absorbing COand acts as a net sink with the disturbed (drained) peatland forest acting as a net source.  Undisturbed forest of Lore Lindu National Park (LLNP) absorbs substantial amount of CO22  with  low ecosystem respiration resulted in a net absorbtion reaching -970 gCm-2 year-1.  Data from a disturbed peatland forest in Central Kalimantan shows that although absorption was higher than the LLNP area ecosystem respiration of this drained peatland resulted in a big net emission reaching 447 gCm-2 year-1.  Recovery of the hydrological system of the area, reduced emission substantially.